2014
DOI: 10.1063/1.4895131
|View full text |Cite|
|
Sign up to set email alerts
|

Inverse cascade and symmetry breaking in rapidly rotating Boussinesq convection

Abstract: International audienceIn this paper we present numerical simulations of rapidly-rotating Rayleigh-Bénard convection in the Boussi-nesq approximation with stress-free boundary conditions. At moderately low Rossby number and large Rayleigh number, we show that a large-scale depth-invariant flow is formed, reminiscent of the condensate state observed in two-dimensional flows. We show that the large-scale circulation shares many similarities with the so-called vortex, or slow-mode, of forced rotating turbulence. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
168
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(206 citation statements)
references
References 57 publications
37
168
1
Order By: Relevance
“…The final geostrophic turbulence regime is dominated by an inverse cascade that generates a depth invariant dipolar vortex which fills the horizontal extent of the computational domain [48]. An identical inverse cascade mechanism was identified previously in stochastically-forced, rotating homogeneous turbulence [52,53], and subsequent DNS studies have demonstrated it as a robust phenomenon in rapidly rotating convection [24,27,60].…”
Section: Introductionmentioning
confidence: 87%
“…The final geostrophic turbulence regime is dominated by an inverse cascade that generates a depth invariant dipolar vortex which fills the horizontal extent of the computational domain [48]. An identical inverse cascade mechanism was identified previously in stochastically-forced, rotating homogeneous turbulence [52,53], and subsequent DNS studies have demonstrated it as a robust phenomenon in rapidly rotating convection [24,27,60].…”
Section: Introductionmentioning
confidence: 87%
“…Instead, we hypothesize that convection occurs in the form of 3-D geostrophic turbulence on smaller scales, whose energy then cascades upwards to larger-scale quasi-2-D flows (e.g. Mininni & Pouquet, 2010;Käpylä et al 2011;Chan & Mayr 2013;Favier et al 2014;Guervilly et al 2014;Rubio et al 2014;Stellmach et al 2014;Nataf & Schaeffer 2015), which are capable of efficiently generating observable magnetic fields. Ultimately, our findings suggest the need to revise current planetary dynamo models to include the effects of multiscale rotating convection dynamics and to determine how such flows produce planetary dynamo action.…”
Section: Discussionmentioning
confidence: 99%
“…The effect is most clearly observed in the stress-free case (Fig 3). The formation of large scale vortices in rotating convection has recently been observed in simulations at larger E [21,22], where the large-scale energy accumulates predominantly in cyclonic structures. Such symmetry breaking is predicted to be absent in the asymptotic small Rossby number case [20].…”
Section: -2mentioning
confidence: 99%